The role of Project-Based Learning (PBL) to promote the development of student's skills for Lifelong Learning [abstract] - Fernandes, Sandra (2024)
This study analyses the impact of Project-Based Learning (PBL) on the development of lifelong learning skills among first-year students at Portucalense University enrolled in the Social Education bachelor's program. [...]